Managements of Exposure to Blood and Body Fluids among Healthcare Workers and Medical Students in University of Gondar Hospital, Northwest of Ethiopia (Global Journal of Medical Research, 2013)
Introduction: Occupational exposures to blood and body fluids in healthcare settings have the potential to transmit hepatitis B virus (HBV), hepatitis C virus (HCV), or human immunodeficiency Virus (HIV). Adherence to standard infection control practices is best way to prevent blood born infections in health care setting. This study tried to assess exposure management practices of HCWs and medical students to blood and body fluids (BBFs) in University of Gondar Hospital. Methods: A cross sectional survey was conducted from September 6 to October 2, 2012, in University of Gondar hospital. Two hundred eighty five participants (including health professionals, janitors and medical students) were participated in the study. Stratified simple random sampling technique was used to select the participants. Data was collected through Self-administered questionnaire and interview using structured questionnaire.
Keywords: occupational exposure; health care workers; blood and body fluid; post exposure management